La contribution des écritures provisoires dans la réussite en orthographe : étude longitudinale - Bégin, Caroline; Saint-Laurent, Lise; Giasson, Jocelyne (Canadian Journal of Applied Linguistics, 2005)
The goals of this study were to: 1) describe the invented spelling produced by Francophone children in Quebec at the beginning of Grade 1; 2) describe the relationship between students’ phonological awareness and their invented spelling; and 3) describe the relationship between students’ invented spelling and conventional spelling. An invented spelling test was administered to 433 Grade 1 students at the beginning of the school year. Others tasks on phonological awareness and spelling were administered. Spelling scores were correlated with phonological awareness (r = 0.539, p < 0.01). Invented spelling scores explained 3% of variance in spelling performance at the end of the year.